2006
DOI: 10.1227/01.neu.0000215944.81730.18
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Magnetic Resonance Imaging Predicts Patient Outcome as an Adjunct to Histopathology: A Second Reference Standard in the Surgical and Nonsurgical Treatment of Low-grade Gliomas

Abstract: Dynamic susceptibility contrast-enhanced perfusion magnetic resonance imaging may be used to identify LGGs that are either high-grade gliomas, misdiagnosed because of sampling error at pathological examination or that have undergone angiogenesis in the progression toward malignant transformation. This suggests that rCBV measurements may be used as a second reference standard to determine the surgical management/risk-benefit equation and postsurgical adjuvant therapy for LGGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 29 publications
4
53
0
Order By: Relevance
“…The ROC curve analysis in the group of astrocytomas corroborates these results and our hypothesis that CBV measurements may be used as an adjunct to histopathology and even as an independent prognostic factor. The latter was also demonstrated by Law et al 10,11 in a mixed population of low-grade gliomas, in which the low-grade oligodendrogliomas had predominantly low perfusion values resembling astrocytomas (in contrast to our study).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The ROC curve analysis in the group of astrocytomas corroborates these results and our hypothesis that CBV measurements may be used as an adjunct to histopathology and even as an independent prognostic factor. The latter was also demonstrated by Law et al 10,11 in a mixed population of low-grade gliomas, in which the low-grade oligodendrogliomas had predominantly low perfusion values resembling astrocytomas (in contrast to our study).…”
Section: Discussionsupporting
confidence: 88%
“…Another limitation is that our study lacks results regarding the predictive role of age, sex, tumor volume, and treatment protocols. Our choice not to analyze these parameters was justified by the small population size (the significance level of the multiple regression analysis including all these factors was P ϭ .08) and the diverse results found regarding age and sex in the literature, 11,17 whereas the predictive role of different treatment protocols has been demonstrated in recent larger studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these parameters have been correlated with tumor grade, aggressiveness, and prognosis. 3,5,7,9 Tumor Blood Volume Regional tumor blood volume measurements reflect an assessment of tumor vasculature and perfusion and have been correlated with glioma grading as well as prognosis. Measurement of tumor blood volume is a good surrogate marker for MVD, a measure of angiogenesis and an important prognostic indicator [10][11][12] in many human cancers.…”
Section: Perfusion Parameters and Their Importancementioning
confidence: 99%
“…The high level of soft tissue contrast makes MR images an important aid in the identification and treatment of gliomas (1)(2)(3). Furthermore, in combination with conventional MR imaging, several studies have shown that dynamic susceptibility contrast (DSC) MR imaging of gliomas is a good presurgical indicator of glioma grade (4 -6) and patient outcome regardless of glioma grade (7,8). Typically, glioma grading from DSC is based on analysis of cerebral blood volume (CBV) values within the glioma area, using either a hot-spot method (4,9) or a histogram analysis method (10,11).…”
mentioning
confidence: 99%